Reading texts for performance and performance as texts shifting paradigms in early English drama studies - King, Pamela M (Routledge, 2021)
"This volume brings together nineteen important articles by Pamela M. King, one of the foremost British scholars working on Early English Drama. Unique to this collection are five articles on the 'living' traditions of performances in Spain, discussing their origins and the modes of production that are used. Several articles use modern literary theory on aspects of early drama, whilst others consider drama in the context of late medieval poetry. The volume also includes a rich collection of articles on English scriptural plays from surviving manuscripts"--